Nicotine treatment produces persistent increases in amphetamine-stimulated locomotor activity in periadolescent male but not female or adult male rats - Collins, Stephanie L.; Montano, Raquel; Izenwasser, Sari (Brain research. Developmental brain research, 2004)
Nicotine is a popular addictive drug used among the adolescent population, and it has long been questioned whether nicotine use in adolescence may lead to the use of other psychostimulant drugs. It is not fully understood, however, how nicotine alters behavior and brain neurochemistry in the adolescent age cohort and how this may affect subsequent illicit drug use. In the current study, periadolescent and adult male and female rats were treated with nicotine for 7 days. One day or 30 days after this treatment, the effects of amphetamine on locomotor activity were studied. Sensitization to nicotine occurred in periadolescent female and adult male and female rats, but not in periadolescent male rats over the course of the 7-day treatment period. On day 8 (1 day after treatment with nicotine ended) and on day 37 (30 days after treatment with nicotine ended), nicotine-pretreated periadolescent male rats were sensitized to the locomotor-activating effects of amphetamine. The response to amphetamine of periadolescent female and adult male and female rats was unchanged at either time point after nicotine pretreatment. Thus, adolescent males are more sensitive than adults or females to the stimulant effects of amphetamine after exposure to nicotine, and this effect is long-lasting. These data suggest that nicotine use during adolescence may carry a greater risk than during adulthood and that male adolescent smokers may be particularly vulnerable to the risk of stimulant abuse.